Odpowiedź :
2h = a pierwiastka z 3
a = 2h / pierwiastek z 3
p = pi r^2
r^2 = p/pi
r = pierwiastek z p/pi
nie wiem o co chodzi w 3 przykladzie napisz mi wiadomosc i opisz dokladniej co tam jest
a = 2h / pierwiastek z 3
p = pi r^2
r^2 = p/pi
r = pierwiastek z p/pi
nie wiem o co chodzi w 3 przykladzie napisz mi wiadomosc i opisz dokladniej co tam jest
h=a√3:2 /*2
2h=a√3/:√3
2h:√3=a
P=πr²/:π
P/π=r²
√(P/π)=r
P=πr(r+l)
P:πr=r+l
P:πr -r=l
2h=a√3/:√3
2h:√3=a
P=πr²/:π
P/π=r²
√(P/π)=r
P=πr(r+l)
P:πr=r+l
P:πr -r=l